Programmed Cell Death-1 Expression in T-Cell Subsets in Chickens Infected with Marek’s Disease Virus - Jumpei Sato; Yoshinosuke Motai; Shunsuke Yamagami; Shwe Yee Win; Fumiya Horio; Hikaru Saeki; Naoya Maekawa; Tomohiro Okagawa; Satoru Konnai; Kazuhiko Ohashi; Shiro Murata (Pathogens)
Marek’s disease virus (MDV) causes Marek’s disease (MD) in chickens, characterized by malignant lymphomas and immunosuppression. Sporadic MD outbreaks continue to occur even among vaccinated flocks in certain regions due to the increased virulence of the field strains. However, the mechanisms of tumorigenesis and immunosuppression caused by MDV remain to be fully elucidated. We previously reported that the mRNA expression of programmed cell death 1 (PD-1), an immune checkpoint molecule, was increased in tumor lesions caused by MDV, and its expression was positively correlated with the mRNA expression of Meq, an MDV-specific oncogene. In this study, we characterized PD-1-expressing T-cell subsets in the spleen and tissues of chickens that developed tumors to investigate the association between PD-1 expression and immunosuppression. Flow cytometric analysis revealed that the proportion of PD-1-expressing CD4+ T-cells, which are targets of MDV tumorigenesis, increased in the spleen and tumor tissues of chickens with MD. The proportion of PD-1+ CD4+ T-cells was higher in Meq-expressing cells than in those that were not. In the spleens of chickens with MD, the proportions of PD-1-expressing cells were increased in CD8+ and γδ T-cells, which play pivotal roles in defense against MD pathogenesis, relative to those of spleens from uninfected chickens. Moreover, the proportion of PD-1+ CD8+ T-cells expressing interferon (IFN)-γ did not increase in the spleen of chickens with MD. Additionally, no difference in the proportion of IFN-γ+ γδ T-cells expressing and not expressing PD-1 was observed in the spleens of chickens with MD, although the proportion of IFN-γ+ γδ T-cells expressing PD-1 in the spleens of uninfected chickens was higher. The function of PD-1-expressing CD8+ and γδ T-cells in chickens may be impaired after developing MD, which may cause MDV-induced immunosuppression.